Constitution & Decentralized Government System in France - Michele; Balthasar Reny Wittermans Un, Yohanes (Universitas Bali Dwipa, 2023)
France is a republican country and uses a semi-presidential unitary government system with democracy which is very inherent in the country. The semi-presidential government system is a combination of the presidential government system and the parliamentary government system, in this case there are two executive leaders, each of whom has their own role. The executive leaders are the President of France who serves as head of state and the prime minister who serves as head of government.The French government system is semi- presidential, the French executive is led by a President who is assisted by a Prime Minister, the French Government is responsible to Parliament based on the provisions of Articles 49 and 50 of the French Constitution. However, the French Parliament consists of the National Assembly and Senate, where the National Assembly has the power to dissolve the cabinetso that the majority determines the choice of the Government, in contrast to Indonesia where Ministers cannot be dismissed by Parliament. The decentralization policy in France is based on a law of the French parliament known as the Gaston Deferred Law of 1982. Concept Autonomous government in France itself is divided into four categories, namely institutional, legal, financial and human resources. In the French Government, the Central Government does not intervene at all when problems arise between the Regional Government and other Regional Governments. The Central Government can act as a mediator but not as a decision-making body, because based on Article 72 of the French Constitution, problems relating to territorial matters are resolved through associations between related parties based on the authority to establish laws.